Hydrogen Production by the Photosynthetic Bacterium Rhodospirillum rubrum - Zürrer, Hans (1979)
Continuous photosynthetic production of hydrogen by Rhodospirillum rubrum in batch cultures was observed up to 80 days with the hydrogen donor, pure lactate or lactic acid-containing wastes, supplied periodically. Hydrogen was produced at an average rate of 6 ml/h per g (dry weight) of cells with whey as a hydrogen donor. In continuous cultures with glutamate as a growth-limiting nitrogen source and lactate as a hydrogen donor, hydrogen was evolved at a rate of 20 ml/h per g (dry weight). The composition of the gas evolved remained practically constant (70 to 75% H(2), 25 to 30% CO(2)). Photosynthetic bacteria processing specific organic wastes could be an advantage in large-scale production of hydrogen together with food protein of high value, compared to other biological systems.